2000
DOI: 10.1103/physrevlett.84.1312
|View full text |Cite
|
Sign up to set email alerts
|

Step-Edge Induced Anisotropic Domain-Wall Propagation

Abstract: We report the observation of anisotropic domain-wall propagation in ultrathin magnetic films with perpendicular anisotropy. A controlled density of step edges was introduced which allowed us to quantify its influence on the domain-wall pinning. For a sawtooth arrangement of the step edges the corresponding wall movement resulted in triangular shaped domains. All aspects of this anisotropic domain-wall evolution could be reproduced by a simulation based on a modified Ginzburg-Landau-type soft-spin model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…4 -6 However, there is no clear physical reason for this. The question on the variations in real films is fundamentally important for exploring a realistic model of the magnetic domain configuration and reversal dynamics, which are known to be sensitive to local magnetic properties as evidenced from recent observations-for instance, for Co films grown on Au͑111͒, 1 Pt/Co/Pt͑111͒ trilayers, 2 and Co/Pd multilayers. 3 It is also a crucial technological issue in achieving a high performance of magnetic information technology, [7][8][9] in which the information is stored in the form of magnetic domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 -6 However, there is no clear physical reason for this. The question on the variations in real films is fundamentally important for exploring a realistic model of the magnetic domain configuration and reversal dynamics, which are known to be sensitive to local magnetic properties as evidenced from recent observations-for instance, for Co films grown on Au͑111͒, 1 Pt/Co/Pt͑111͒ trilayers, 2 and Co/Pd multilayers. 3 It is also a crucial technological issue in achieving a high performance of magnetic information technology, [7][8][9] in which the information is stored in the form of magnetic domains.…”
mentioning
confidence: 99%
“…[1][2][3][4] Due to the lack of available techniques capable of providing detailed information about the variations with a high spatial resolution, the variations are typically considered under an assumption of the Gaussian ͑or Lorentzian͒ distribution in most theoretical approachesfor instance, Preisach and micromagnetic modeling. 4 -6 However, there is no clear physical reason for this.…”
mentioning
confidence: 99%
“…[25][26][27] The previous stochastic elements, however, have not been comprehensively addressed in earlier experimental efforts in which single shot measurements were dominant. [17][18][19][20][21][22][23][24] Consequently, accurate decoding of the potential profile from these seemingly random domain configurations was not possible.…”
Section: Introductionmentioning
confidence: 96%
“…[11][12][13][14][15][16] While the underlying cause of DW pinning by crystalline defects has been known for nearly a century as the Barkhausen effect, 1-4 the direct experimental evaluation of the potential profiles created by the randomly distributed and magnetically active pinning sites in macroscopic system is currently a great challenge. [17][18][19][20][21][22][23][24][25][26][27] Note that conventional structural characterization tools offer a direct measure of the presence of various defects; however, their experimental links to the pinning potential remained elusive. This stems from the competitive interactions that lead to the stochastic pinning/depinning of DWs, which is a manifestation of the system's complex energy landscape with an infinite number of metastable states.…”
Section: Introductionmentioning
confidence: 98%
“…Studies on Co, Pt, and Fe [3][4][5][6] demonstrated that variations of the film thickness even down to the monolayer scale can pin a magnetization domain wall (DW)…”
mentioning
confidence: 99%